EARLY EDUCATION AND CARE - THE PERSPECTIVE OF ROMANIAN PRE-UNIVERSITY EDUCATION - Emil LAZĂR (Universitaria Publishing House, Craiova, 2021)
This paper is intended as an attempt to equally surprise both the notions of the conceptual apparatus and the historicity of early education from the Romanian perspective. This conceptual approach, respects and relates itself, to the European and worldwide pedagogical concepts, the way they are understood and promoted in the light of educational policies. The Romanian reality in the field of early education, may be and it is, authentic and innovating: authentic, based on the specific of educational policies, innovating, by the development and emergence of this segment of educational responsibility in Romania. Therefore, Romania offers and constitutes an example of good practice.